2015
DOI: 10.1038/mi.2014.72
|View full text |Cite
|
Sign up to set email alerts
|

A small intestinal organoid model of non-invasive enteric pathogen–epithelial cell interactions

Abstract: Organoids mirror in vivo tissue organization and are powerful tools to investigate the development and cell biology of the small intestine. However, their application for the study of host-pathogen interactions has been largely unexplored. We have established a model using microinjection of organoids to mimic enteric infection, allowing for direct examination of pathogen interactions with primary epithelial cells in the absence of confounding variables introduced by immune cells or the commensal microbiota. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
140
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(151 citation statements)
references
References 42 publications
(69 reference statements)
3
140
1
Order By: Relevance
“…Recently, others have utilized mouse-derived enteroids (epithelium-only organoids) to study host-microbe interactions (29,30). A key difference between those reports and the data presented here is that our system utilizes organoids derived from human cells rather than mouse intestinal crypts.…”
Section: Discussioncontrasting
confidence: 44%
“…Recently, others have utilized mouse-derived enteroids (epithelium-only organoids) to study host-microbe interactions (29,30). A key difference between those reports and the data presented here is that our system utilizes organoids derived from human cells rather than mouse intestinal crypts.…”
Section: Discussioncontrasting
confidence: 44%
“…It is practical to use a 3-dimensional manipulator instead of a 2 dimensional manipulator to allow maximal flexibility to reach into the wells. Oil-based microinjectors (such as Celltram, or IM-5B) provide a finer and slower manual control compared to air-based microinjectors (such as FemtoJet 11 , or Nanojet microinjector 10 ). In turn, the latter have the important advantage that a precise injection volume can be programmed.…”
Section: Discussionmentioning
confidence: 99%
“…They have been used to model infections with viruses, such as Cytomegalovirus 1,2 or Hepatitis C Virus [3][4][5][6][7] , parasites, such as Plasmodium falciparum 8 or Toxoplasma gondii 9 , and bacteria, such as Bacterioides thetaiotaomicron 10 or Salmonella enterica 11 . Most recently, several approaches have been published to model infection with H. pylori with organoids derived from ESC or iPS cells 12 , mouse adult stem cells 21,22 or human adult stem cells [13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…Co-cultures of mouse small intestinal organoids with Escherichia coli have been used to investigate the effects of antimicrobial products on the dynamics and function of Paneth cells . Moreover, human intestinal organoids were exploited to functionally characterize several cholera toxin inhibitors (Zomervan Ommen et al, 2016), while two recent studies employed mouse intestinal organoids to model Salmonella infections (Wilson et al, 2015;Zhang et al, 2014). In addition to an NFκB-induced inflammatory response, the authors observed disruption of epithelial tight junctions and downregulation of ISC markers Lgr5 and Bmi1 in Salmonella-infected organoids (Zhang et al, 2014).…”
Section: Host-pathogen Interactionsmentioning
confidence: 99%